Oviposition Preference of Bactrocera dorsalis Hendel (Diptera: Tephritidae) on Different Fruit in Snake Fruit Orchard - Rahmi Fitrah; Deni Pranowo; Suputa Suputa (Universitas Gadjah Mada, 2020)
The oriental fruit fly Bactocera dorsalis (Hendel) is an important pest of snake fruit (Salacca zalacca) in Sleman District. Due to the high level of damage by the fruit flies, it is necessary to do. The aim of this research was to find out suitable fruit traps, by testing the oviposition preferences of the fruit flies in the orchard to lay eggs on several types of fruit. The research was done in snake fruit orchard located at Sleman Yogyakarta and owned by farmers, while the Lab works were done at the Laboratory of Entomology, Department of Plant Protection, Faculty of Agriculture, Universitas Gadjah Mada. All researches were done between April-June 2019. Guava (Psidium guajava), watery rose apples (Syzygium aqueum), starfruit (Averrhoa carambolae), and snake fruit (Salacca zalacca) were used as trap crops. Each fruit, with the same maturity level, was hung 1.5 m above the ground for 4 days with 12 days total trapping at intervals of 3 times. After the test, each fruit was taken and the insects in it were reared in the laboratory. The number of pupae and flies that emerged from each fruit was counted and compared. The results showed that in the orchard 1 as well as 2, of guava fruit produced the highest number of (151 pupae) followed by salak (94 pupae), star fruit (83 pupae), and water guava (2 pupae). The finding of seeds shows that guava fruit is the most suitable host for the fruit flies to be used in the trapping, followed by star fruit and watery guava.